Self-Polymerization Reaction of Epoxidized Oleic Acid: Kinetic and Product Characterization - Dyah Retno Sawitri; Panut Mulyono; Rochmadi Rochmadi; Arief Budiman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Epoxidized oleic acid can be transformed into vegetable oil-based polyesters through a self-polymerization reaction. This study aims to develop the kinetic model for the polymerization reaction between epoxide and carboxyl groups and the product characterization regarding its functional groups, molecular weight, and thermal stability. The polymerization reaction was carried out at the temperature of 120–180 °C for 2–6 h with the highest conversion of oxirane number up to 97%. Kinetic study showed one-step reaction model between oxirane and carboxylic group gives the activation energy value of 34.71 kJ/mol. Furthermore, the two simultaneous reaction model with further reaction between oxirane group and hydroxyl group also taken into account. The later provides a better agreement between the experimental data and the calculated conversion value. The activation energy values in the first and second steps are 38.61 and 26.00 kJ/mol, respectively. The product characterization showed that adding adipic acid did not significantly affect the polymer's molecular weight and thermal stability. The polydisperse characteristics of the poly(oleic acid) produced in this study enable poly(oleic acid) to be used as a lubricant, a polymer additive, or a precursor to produce polymers with higher molecular weights by taking advantage of the accessibility of OH groups. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).